Desain Pembelajaran Model Jigsaw Terhadap Kemampuan Pemahaman Konsep Matematis dan Self-Efficacy Siswa - Lukman El Hakim; Sofyan Husein Nasution; Tian Abdul Aziz; Flavia Aurelia Hidajat (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This article aims to develop an instructional design in applying the Jigsaw cooperative learning model to the ability to understand mathematical concepts and the self-efficacy of students at SMK N 26 Pembangunan Jakarta. The learning material chosen is lines and series, covering the following sub-topics: Arithmetic series, geometric series, arithmetic series, and geometric series. The steps before forming the instructional design carried out a needs analysis in which classroom observations and teacher and student interviews were carried out. After the needs analysis is obtained, a learning plan is formed that will be created and will be implemented in the next lesson.